2015
DOI: 10.1021/acs.jpcb.5b04732
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Catalytic Mechanism Involved in the Isocitrate Lyase Superfamily: Hybrid Quantum Mechanical/Molecular Mechanical Calculations on 2,3-Dimethylmalate Lyase

Abstract: The isocitrate lyase (ICL) superfamily catalyzes the cleavage of the C(2)-C(3) bond of various α-hydroxy acid substrates. Members of the family are found in bacteria, fungi, and plants and include ICL itself, oxaloacetate hydrolase (OAH), 2-methylisocitrate lyase (MICL), and (2R,3S)-dimethylmalate lyase (DMML) among others. ICL and related targets have been the focus of recent studies to treat bacterial and fungal infections, including tuberculosis. The catalytic process by which this family achieves C(2)-C(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…The figure showed that a concerted catalytic mechanism is unlikely since the deprotonation of isocitrate C(2)–OH and a proton transfer to the acceptor residue occurs before the elongation of the C(2)–C(3) bond and thereafter leading to bond breaking. This is consistent with the observation for the mechanism of DMML, a subclass of the lyase family 16 . The starting structure for the non-constrained transition state was obtained from the scan coordinate (Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The figure showed that a concerted catalytic mechanism is unlikely since the deprotonation of isocitrate C(2)–OH and a proton transfer to the acceptor residue occurs before the elongation of the C(2)–C(3) bond and thereafter leading to bond breaking. This is consistent with the observation for the mechanism of DMML, a subclass of the lyase family 16 . The starting structure for the non-constrained transition state was obtained from the scan coordinate (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In DMML, Arg161 (corresponding to Arg228 of M. tuberculosis ICL) was reported to be potentially responsible for the deprotonation of isocitrate C(2)–OH which leads to the cleavage of isocitrate C(2)–C(3) bond 16 , 20 . However, our study showed alternative findings as ICL Arg228 is already in the protonated state and could not serve as a proton shuttle from isocitrate C(2)–OH that leads to the isocitrate cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations